Weight bias among primary care health professionals: personal attitude matters - (:unkn) unknown (EDITRICE KURTIS S R L, 2010)
Background and aims: Weight bias contributes to the production of health disparities. This study aims to investigate attitudes and professional practice patterns of primary health care providers towards obese patients. Methods: This study was designed as a cross-sectional survey carried out among primary care health professionals (PCHP) in one district of Istanbul. Among the total 134 doctors and nurses approached, 104 gave consent to participate (77.6%). All participants filled in a 24 item obesity perception survey (OPS) which contained two subtopics: personal attitudes and professional practice patterns. Participants were asked to rate each statement in the survey according to a 5 point Likert scale (from 0: totally disagree, to 5: totally agree). Results: Among the participants 23.1% (n=24) were male and 50.9% were physicians (n=53). The Cronbach's alpha for the whole perception scale was 0.86. Significantly more nurses than physicians do not want to work with (chi(2)=4.62; p=0.032) and prefer not to provide service to an obese person (chi(2)=8.17; p=0.004). When independent variables such as the personal attitudes subtopic score, body mass index, age, gender, professional status (nurse or doctor) and years of work experience were put in the stepwise linear regression analysis, the personal attitudes score was found to be accountable for 64% of the variance for professional practice patterns score (adjusted R(2)=0.64, p<0.000; B +/- SE: 0.69 +/- 0.05). Conclusions: Our findings showed that obesity elicited some negative attitudes from PCHPs and the professional practice patterns towards obese patients were associated with personal attitudes to a large extent. Obesity and Metabolism 2010; 6: 63-68.
Keywords: Attitude; obesity; professionalism; weight bias; OBESITY; DISCRIMINATION; STIGMA; MANAGEMENT; PHYSICIANS; PREJUDICE; VIEWS